1998
DOI: 10.1093/ps/77.6.888
|View full text |Cite
|
Sign up to set email alerts
|

Use of a sperm analyzer for evaluating broiler breeder males. 1. Effects of altering sperm quality and quantity on the sperm motility index

Abstract: A new instrument for assessing mammalian semen attributes, the Sperm Quality Analyzer, was evaluated as a potential tool for determining rooster sperm quality. The Sperm Quality Analyzer measures the "activity" of sperm in a semen sample as the sperm motility index (SMI). The SMI is defined as the number and amplitude of deflections in a light path per second as a result of sperm movement within a capillary tube. In the present study, effects of sperm concentration, viability, and motility on the SMI were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 12 publications
2
21
0
1
Order By: Relevance
“…An asterisk indicates a signi cant difference between control and heat stressed males for a given week. SQI values produced a greater proportion of fertilised eggs in the current study, as in past research (McDaniel et al, 1998;Parker et al, 2000Parker et al, , 2002. However, in the present study, males with higher SQI values were more affected by high temperature than males with lower values.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…An asterisk indicates a signi cant difference between control and heat stressed males for a given week. SQI values produced a greater proportion of fertilised eggs in the current study, as in past research (McDaniel et al, 1998;Parker et al, 2000Parker et al, , 2002. However, in the present study, males with higher SQI values were more affected by high temperature than males with lower values.…”
Section: Discussionsupporting
confidence: 71%
“…Heat stress can cause signi cant decreases in rooster fertility due to a decrease in semen quality and the number of sperm penetrating the perivitelline membrane (Clark and Sarakoon, 1967;McDaniel et al, 1995McDaniel et al, , 1996. The sperm quality index (SQI) is correlated with rooster fertility (McDaniel et al, 1998;Parker et al, 2000) and, on average, declines when roosters are heat stressed (Hood, 1999;Karaca, 2001). However, it is possible that males with different semen qualities prior to heat exposure may respond differently to heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Peebles and Brake (1985) concluded that feeding ascorbic acid to broiler breeder at the rate of 50 ppm/kg feed improved fertility compared to the control group. In contrast, McDaniel et al (1998) reported that ascorbic acid (500 ppm/kg feed) did appear to improve semen quality and fertility. Elansary et al (1999) reported increased ejaculated volume, sperm concentration and sperm motility in vitamin C fed cockerels compared to the control.…”
Section: Vitamin Cmentioning
confidence: 89%
“…The age-old method of sperm motility measurement is the microscopic method that essentially measures horizontal motion of the cells and this method gives only a subjective assessment of sperm motility. Subsequently several objective methods have been developed to measure sperm horizontal movement, the CASA being the most widely used one (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Although CASA gives multiple sperm motility parameters, their correlation with fertility potential of spermatozoa is not well defined (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…In the present international scenario, microscopic method is the most widely used subjective method for sperm motility analysis. Subsequently, more objective methods were developed, such as light scattering method, laser beam method, multiple exposure photographic method, etc (14)(15)(16)(17)(18)(19)(20)(21)(22). But, all the available techniques consider only the ''horizontal'' velocity and there is not a single instrument available for measuring the ''vertical'' velocity of spermatozoa.…”
mentioning
confidence: 99%